Transforming Workplaces Through Diversity, Equity, and Inclusion: A Path to Employee Engagement and Commitment - Kalla, Rastina; Alam, Roslina; Loreño, Dustin Tarinque (Universitas Brawijaya, Indonesia, 2025)
In Indonesia's tourism industry, where workforce diversity is high and service excellence is essential, the urgency to implement inclusive and equitable workplace practices is increasingly critical. Many tourism businesses still struggle to translate diversity, equity, and inclusion (DEI) efforts into meaningful employee outcomes, creating a pressing need for empirical investigation. This study aims to examine the influence of Diversity, Equity, and Inclusion on employee engagement and organizational commitment, incorporating psychological safety as a mediating variable and leadership style as a moderating variable. A quantitative research design was adopted using Structural Equation Modeling-Partial Least Squares (SEM-PLS). Data were collected through purposive sampling from 350 employees in hotels, travel agencies, and hospitality services across Indonesia, all with at least one year of experience in the tourism sector. The analysis confirms that Diversity, Equity, and Inclusion significantly enhances employee engagement and commitment. Psychological safety serves as a robust mediator, while leadership style significantly strengthens these relationships. Furthermore, both engagement and commitment positively affect employee retention. The study’s novelty lies in modeling Diversity, Equity, and Inclusion as a higher-order construct and empirically testing its indirect and interaction effects in the context of Indonesia's tourism industry. These findings make theoretical contributions to the Diversity, Equity, and Inclusion literature and provide practical insights for promoting inclusive workplace policies that foster long-term workforce stability.